2009
DOI: 10.1002/jcu.20601
|View full text |Cite
|
Sign up to set email alerts
|

Sonography versus nerve conduction studies in patients referred with a clinical diagnosis of carpal tunnel syndrome

Abstract: NCS show better sensitivity than US in supporting a diagnosis of CTS. However, because of its high positive predictive value, one may consider using US as a screening test, eliminating the need for NCS in the majority of clinical suspicion of CTS and reserving NCS for cases in which US is negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 20 publications
3
62
0
3
Order By: Relevance
“…We agree with the results found by the authors and according to the trend showed in the literature, there is an increased interest on this topic [2][3][4] that demonstrates that US is able to detect median nerve damage in a very easy, non-invasive and non-expensive way.…”
supporting
confidence: 94%
“…We agree with the results found by the authors and according to the trend showed in the literature, there is an increased interest on this topic [2][3][4] that demonstrates that US is able to detect median nerve damage in a very easy, non-invasive and non-expensive way.…”
supporting
confidence: 94%
“…Patients without clinical signs and symptoms of CTS may still have inflammation and thickening of the median nerve (only 4% of asymptomatic patients will have abnormal ultrasound examinations), but the changes have not yet caused clinical symptoms and signs [19]. Studies using EDX as the gold standard have substantial false-positive and false-negative rates [4,9,10,14,[22][23][24]. Third, the use of ROCs to determine optimal cutoff values for the diagnosis of CTS also clouds the interpretation of data.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies used a constellation of clinical findings as the reference standard to determine the presence of CTS [1,5,12,14,[22][23][24]27]. The sensitivity and specificity reported in these studies ranged from 62% to 98% and 63% to 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,16,26,28) Our ROC analysis yielded a cut-off value of 9 mm 2 with 86.7% sensitivity and 88.9% specificity. Those results are similar to previous reports and comparable with sensitivities and specificities of the EDT results.…”
Section: Discussionmentioning
confidence: 80%
“…14) Anatomical variations of median nerve and other morphological changes, such as cysts, neuromas, and aberrations of muscles and nerves, at the wrist are relatively common. 1,4,8,13,16) Therefore USG can provide an anatomical profile which is important when minimal invasive surgery, such as endoscopic median nerve release, is performed. Mean normal value of median nerve CSA at the carpal tunnel inlet have varied among reports, ranging from 6.1 to 10.4 mm 2 .…”
Section: Discussionmentioning
confidence: 99%